Edukasi TBC pada Masyarakat dan Kelompok Lansia Di Masa Covid-19 di Kelurahan Sumur Batu, Jakarta - Ndaru Andri Damayanti; Elfitri Kurnia Erza; Risdawati Johan (Lembaga Penelitian Universitas YARSI, 2020)
Health education activities for the transmission and prevention of TB and Covid-19 to the elderly group of Sumur Batu Village have been completed online on Saturday morning, August 8, 2020 for 3 hours. TB education activities during the Covid-19 pandemic motivated the elderly and the community to continue treating TB. Respondents who joined were not only the elderly and the general public living around the RPTRA Mutiara, Sumur Batu Village, but also joined several colleagues from YARSI, with a total of 52 participants. The results of the pre and post-test through the questionnaire showed an increase rate for all extension participants by 84%. Evaluation of satisfaction with extension activities was appreciated with satisfactory and very satisfying criteria.